Climate change adaptation: What is driving us into action? - Monika Mačiulienė; Aelita Skaržauskienė; Kristina Kovaitė (Contemporary Economics, 2025)
The growing frequency of climate-related events underscores the urgent need for effective adaptation strategies alongside mitigation efforts. This study investigates the motivations driving climate adaptation behaviors in Lithuania, a region less immediately affected by climate change impacts. Drawing on survey data from 1,013 respondents, the research applies established theoretical frameworks, including the Theory of Planned Behavior and Value-Belief-Norm Theory, to analyze economic, ecological and social motivators for adaptation actions. Results reveal that financial considerations, such as affordability and incentives, are the strongest drivers, followed by social influences, including interpersonal encouragement and moral satisfaction. Ecological motivations, while impactful, are predominantly linked to actions with visible local environmental benefits. Demographic analyses highlight age-related differences in motivations, with younger respondents displaying higher ecological and economic concerns, and gendered patterns showing females prioritizing social and ecological values. The findings emphasize the importance of localized strategies that align interventions with dominant motivators and demographic preferences, fostering inclusive and effective climate adaptation policies. This study contributes a nuanced understanding of adaptation behaviors in less vulnerable regions, offering insights for targeted communication and policy design.
Keywords: I31; 330; climate-related hazards; worldviews; motivation; citizen climate adaptation; adaptation actions